Inflammatory myofibroblastic tumour of the urinary bladder managed with partial cystectomy: a case report & literature review. (1st November 2016) - Nkwam, Nkwam; Johnson, Bethan; Bazo, Alvaro; McCulloch, Tom A.; Mann, Gurminder S.
Abstract: Inflammatory myofibroblastic tumour (IMT) is a rare neoplasm which can affect many different organs throughout the body. We report the case of a 62-year old female presenting with visible haematuria found to have IMT of the urinary bladder exhibiting anaplastic lymphoma kinase-1 gene rearrangement, initially managed with local resection and then definitively with partial cystectomy.